LEGAL ANALYSIS OF APPLICATION FOR DIVORCE AND WIFE RECONVENTION CLAIMS AT BANYUWANGI RELIGIOUS COURT - Mulyanto, Rudi (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2022)
At first 10 (ten) cases studied by the author were cases of divorce applications. However, in the trial process, the wife filed a counterclaim called a reconvention lawsuit to claim her rights. The rights demanded are such as living, mut'ah, iddah, madhiyah, or hadhanah as well as gono-gini assets. However, not all counterclaims were granted by the panel of judges based on various considerations. To find out, the researcher formulated two problem formulations, namely: 1. How is the legal protection for the plaintiffs of reconciliation if their rights are not obtained in accordance with the Court's decision which has permanent legal force, 2. Can the implementation of the Court's decision be carried out effectively.This research is an empirical research that uses descriptive analysis method with a qualitative approach. Sources of data were collected through interviews with several relevant informants, namely the panel of judges, the Registrar of the Banyuwangi Religious Court. Literature and documentation in the form of copies of decisions, books were also used as further data sources. After the data is collected, the data is processed by editing, classifying, and grouping according to the problem formulation. Then, it is reviewed and analyzed by connecting the data and literature review.The conclusions of this study are: 1) Efforts to protect the wife by providing a living have been carried out to the maximum. However, these efforts do not always run smoothly, because the husband does not make it happen. In article 34 of Law Number 1 of 1974 in conjunction with article 80 (4) the Compilation of Islamic Law, it has been determined about the kinds of rights that a wife can claim when divorced by her husband in court, and if the husband is unable to fulfill the expenses decided by the Religious Court, the panel of judges will postpone the implementation of the ikrtalak for 6 (six) months. 2) The implementation of the Court's decision is not all carried out effectively and according to expectations, this is due to the husband's mediocre level of economic ability.